Characterization and cause analysis of the "bright spots" on the surface of a GH2674 large-size gas turbine disk. (October 2022) - Zhang, H.Y.; Qu, S.; Dong, C.; Wang, X.G.; Fu, C.M.; Zhang, Z.F.
Highlights: The bright spots have not been reported before. The characteristics and cause of the bright spots are detailly analyzed. The bright spots are essentially freckle defects, and their effects on tensile and fatigue properties are analyzed by mechanical tests. X-ray tomography was utilized to illustrate the distribution of the precipitates in the spot region and the depth was quantitively measured. The in-situ fatigue test shows the large-size MC carbides and Laves phases could promote the fatigue crack initiation. Abstract: After surface turning process, many surface defects (visually shown as "bright spots") were found on both sides of the large-size turbine disk. Macro- and microscopic inspections illustrated the distribution of the spots, hardness variation and morphologies inside the spot regions. MC carbides, Laves phases, Mo2 C carbides, η phases, G phases were found in the spot regions by SEM, TEM and EDS. The depth of the aggregated precipitates was shown by 3D X-ray tomography. It is indicated that the optic difference of the "bright spots" is due to the change of surface roughness after the cutting tool passed through the segregation regions with higher hardness. The bright spots are essentially freckle defects, which originated from the Ti segregated zones in the ingot. The effect of these defects on the tensile and fatigue properties were further analyzed. The remedial methods are then proposed to alleviate the detrimental effect of the bright spots.